Relationships between fitness status and match running performance in adult women soccer players: A cohort study - Gonçalves, L.; Clemente, F. M.; Barrera, J. I.; Sarmento, H.; González-Fernández, F. T.; Palucci Vieira, L. H.; Figueiredo, A. J.; Clark, C. C. T.; Cancela Carral, J. M. (Medicina, 2021)
Background and Objectives: The aim of this study was twofold: (i) to analyze the relationships between fitness status (repeated-sprint ability (RSA), aerobic performance, vertical height jump, and hip adductor and abductor strength) and match running performance in adult women soccer players and (ii) to explain variations in standardized total distance, HSR, and sprinting distances based on players` fitness status. Materials and Methods: The study followed a cohort design. Twenty-two Portuguese women soccer players competing at the first-league level were monitored for 22 weeks. These players were tested three times during the cohort period. The measured parameters included isometric strength (hip adductor and abductor), vertical jump (squat and countermovement jump), linear sprint (10 and 30 m), change-of-direction (COD), repeated sprints (6 × 35 m), and intermittent endurance (Yo-Yo intermittent recovery test level 1). Data were also collected for several match running performance indicators (total distance covered and distance at different speed zones, accelerations/decelerations, maximum sprinting speed, and number of sprints) in 10 matches during the cohort. Results: Maximal linear sprint bouts presented large to very large correlations with explosive match-play actions (accelerations, decelerations, and sprint occurrences; r = -0.80 to -0.61). In addition, jump modalities and COD ability significantly predicted, respectively, in-game high-intensity accelerations (r = 0.69 to 0.75; R2 = 25%) and decelerations (r = -0.78 to -0.50; R2 = 23-24%). Furthermore, COD had significant explanatory power related to match running performance variance regardless of whether the testing and match performance outcomes were computed a few or several days apart. Conclusion: The present investigation can help conditioning professionals working with senior women soccer players to prescribe effective fitness tests to improve their forecasts of locomotor performance.